Preference Of Analgesic Drug For Pain Control Following Extraction Of Teeth - A Retrospective Study - KARTHIKEYAN, HARIPPRIYA; PRABHU, ABHINAV RAJENDRA; RAMANATHAN, VISALAKSHI (The journal of contemporary issues in business and government, 2020)
The aim of this retroperspective study was to assess the preference of analgesic drugs administered for pain control following dental extraction of teeth. The study was conducted in a University based setting.The study group of this research were patients who reported to the clinics with moderate to severe toothache/ dental pain who required tooth extraction.Case sheets were reviewed between June 2019 to March 2020.Data were analyzed using SPSS software (IBM SPSS Statistics, Version 24.0, Armonk, NY: IBM Corp). Chi square test was applied to find the association between the parameters and the level of significance.A total of 7888 patients were involved in this study. 45.7% were female patients and 54.3% were male patients. About 70.3% of the population falls in the age category 21-60 years.Around 45.8% of the population were prescribed with Paracetamol. The commonly prescribed combination analgesic of choice was Paracetamol and Aceclofenac for 26.6% of the patients. We conclude that middle aged patients in the age group 21- 60 years were prescribed Paracetamol as the first analgesic of choice for postoperative dental pain control.